2006
DOI: 10.1099/mic.0.28782-0
|View full text |Cite
|
Sign up to set email alerts
|

Irr regulates brucebactin and 2,3-dihydroxybenzoic acid biosynthesis, and is implicated in the oxidative stress resistance and intracellular survival of Brucella abortus

Abstract: Brucella abortus faces iron deprivation in both nature and the host. To overcome this limitation, Brucella secretes the siderophores 2,3-dihydroxybenzoic acid and brucebactin. A Fur-like protein named Irr has previously been characterized in B. abortus; this protein is present in the a-2 group of Proteobacteria only, where it negatively regulates haem biosynthesis when iron is scarce. Additional evidence that Irr also regulates the synthesis of both siderophores is presented here. Transcriptional lacZ fusion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 35 publications
1
45
1
Order By: Relevance
“…We measured the sensitivity of our mutants to SNG and H 2 O 2 and found that the sensitivity profiles of the single mutants corresponded to the amount of uncomplexed iron as measured by EPR; decreased iron in the irr mutant correlated with increased SNG/H 2 O 2 resistance, and increased iron in the rirA mutant correlated with decreased resistance. Increased H 2 O 2 resistance in an irr mutant has also been observed in Brucella abortus (36). The ⌬irr ⌬rirA double mutant does not universally follow the rule of increased uncomplexed cellular iron resulting in increased sensitivity, as it has a slightly increased EPR-detectable iron concentration but low SNG sensitivity.…”
Section: Discussionmentioning
confidence: 80%
“…We measured the sensitivity of our mutants to SNG and H 2 O 2 and found that the sensitivity profiles of the single mutants corresponded to the amount of uncomplexed iron as measured by EPR; decreased iron in the irr mutant correlated with increased SNG/H 2 O 2 resistance, and increased iron in the rirA mutant correlated with decreased resistance. Increased H 2 O 2 resistance in an irr mutant has also been observed in Brucella abortus (36). The ⌬irr ⌬rirA double mutant does not universally follow the rule of increased uncomplexed cellular iron resulting in increased sensitivity, as it has a slightly increased EPR-detectable iron concentration but low SNG sensitivity.…”
Section: Discussionmentioning
confidence: 80%
“…However, the affinity of Irr for those DNA elements is very weak in vitro (21). In fact, in vitro binding studies of Irr from several organisms all require micromolar concentrations of protein to detect DNA binding (3,14,21,27). Herein, we show that Irr is a transcriptional repressor with high affinity for target DNA and that Irr occupies the promoters of target genes in vivo.…”
mentioning
confidence: 92%
“…A role for Irr as both a positive and a negative global regulator is based on several observations. Irr was initially discovered as a positive effector of ferric iron transport as well as a negative regulator of heme biosynthesis (11), and similar roles have been described for Brucella abortus Irr (13,14). Microarray analysis of a B. japonicum irr mutant shows that Irr affects the expression of many iron-regulated genes, and a heme-defective strain cannot maintain normal iron homeostasis (27).…”
mentioning
confidence: 99%
“…(Anderson et al, 2011;Paulley et al, 2007). When a different B. abortus irr mutant was previously tested in Balb/C mice, at 7 and 21 days after inoculation, neither the increment in catalase activity and haem content, nor the decline in siderophores biosynthesis affected the wild type virulence (Martinez et al, 2006). Although a different mice strain was used, the attenuation in the brucella virulence observed after 4 weeks p.i.…”
Section: In Animalsmentioning
confidence: 99%
“…However, experimental evidence on mutants unable to synthesize those molecules failed to demonstrate that their production is critical for bacterial replication inside macrophages (Bellaire et al, 1999;Jain et al, 2011). In addition, a mutant in the main iron-response regulator gene, with deficient synthesis of siderophores and increased intracellular haem content, showed a better replication pattern inside professional phagocytes than wild type (Martinez et al, 2006). On the other hand, a B.…”
Section: Introductionmentioning
confidence: 99%